HUBUNGAN LINGKUNGAN KERJA DENGAN KEPUASAN KERJA PERAWAT DI RUMAH SAKIT UNIVERSITAS ISLAM INDONESIA YOGYAKARTA - Istichomah, Istichomah; Dhanang Kurniawan, Muhammad; Retno Wulandari, Setyo; Handayani, Sri (NHM PRESS, 2025)
Background: Nursing services are a determining factor in the success of health services in hospitals, because in almost every country up to 80% of health services are provided by nurses. As many as 40% of health service providers in Indonesia are nursing staff Objective: The purpose of this study was to determine whether there is a relationship between the Work Environment and job satisfaction of nurses at UII Bantul Hospital, Yogyakarta. Method: This study was conducted cross-sectionally using the entire sample. This study involved 160 nurses working in the outpatient and inpatient departments of UII Bantul Hospital, Yogyakarta. Data collection through surveys can be accessed via a link to Google Forms. Results: Data analysis was carried out using Spearman rank test analysis. The results of the study showed a good work environment. As many as 76 respondents stated that they were satisfied with their jobs, and 10 (6.3%) stated that they were dissatisfied with their jobs. The results showed a Spearman Rho correlation value of 0.332 and a p-value of 0.000 less than 0.05. This indicates that both are positive or heading in the same direction, although at a weaker level. Conclusion: There is a significant and unidirectional relationship between the work environment and the satisfaction of nursing staff in the outpatient and inpatient rooms of UII Bantul Hospital, Yogyakarta.